Republic of Moldova : Financial Sector Assessment Program-Bank Crisis Resolution-Technical Note. (IMF Staff Country Reports; Country Report, 2016)
An important aspect of the FSAP mission was the review of the bank crisis resolution framework in Moldova. There are several characteristics of vulnerabilities in the banking system which suggests the need for the authorities to give a high priority to crisis resolution preparedness. Notable in this context is the concentrated nature of the banking system, being dominated by six domestic banks (four of which are relatively large): the six banks, which de facto appear to form two groups of banks (involving five of the six largest domestic banks) having combined market share of 60-70 percent of banking system assets. In the case of two of these banks there is a significant large exposure risk, with aggregate large exposures being well in excess of the banks' capital. These banks also have relatively large exposure risk to foreign banks. Moreover, stress testing undertaken for the FSAP suggests a potential vulnerability to credit risks, particularly as regards foreign currency denominated loans.